Disappearance rate of a peatland in Dublany near Lviv (Ukraine) drained in 19th century - K. Lipka; E. Zając; V. Hlotov; Z. Siejka (Mires and Peat, 2017)
We aimed to determine the rate of subsidence of a peatland over 133 years since its drainage, and to evaluate the relative contributions of compaction and oxidation to this process. Reliable determination of this proportion is problematic. The results of our calculation were applied to estimate CO2 emissions by two approaches, assuming different oxidation fractions. The surface of the fen was lowered by 47.9 %, i.e. 2.0 cm year-1, of which about 60 % was due to oxidation and 40 % due to compaction. The process was more intense around a peat mining area, where the surface lowering was greater and the ratio of compaction to oxidation was about 30:70. Our results for the share of oxidation were in line with values most often reported in the literature for warm temperate climate zones. Therefore, the method used for assessing it may be considered reliable.